Risk factors for osteoporotic fractures and low bone density in pre and postmenopausal women Factores de riesgo para fractura por osteoporosis y baja densidad ósea en mujeres en la pre y post menopausia Fatores de risco para fratura por osteoporose e baixa densidade óssea em mulheres na pré e pós-menopausa - Marcelo M Pinheiro; Edgard T dos Reis Neto; Flávia S Machado; Felipe Omura; Jeane H K Yang; Jacob Szejnfeld; Vera L Szejnfeld (Universidade de São Paulo, 2010)
OBJECTIVE: To estimate the prevalence and analyze risk factors associated to osteoporosis and low-trauma fracture in women. METHODS: Cross-sectional study including a total of 4,332 women older than 40 attending primary care services in the Greater São Paulo, Southeastern Brazil, between 2004 and 2007. Anthropometrical and gynecological data and information about lifestyle habits, previous fracture, medical history, food intake and physical activity were obtained through individual quantitative interviews. Low-trauma fracture was defined as that resulting from a fall from standing height or less in individuals 50 years or older. Multiple logistic regression models were designed having osteoporotic fracture and bone mineral density (BMD) as the dependent variables and all other parameters as the independent ones. The significance level was set at p<0.05. RESULTS: The prevalence of osteoporosis and osteoporotic fractures was 33% and 11.5%, respectively. The main risk factors associated with low bone mass were age (OR=1.07; 95% CI: 1.06;1.08), time since menopause (OR=2.16; 95% CI: 1.49;3.14), previous fracture (OR=2.62; 95% CI: 2.08;3.29) and current smoking (OR=1.45; 95% CI: 1.13;1.85). BMI (OR=0.88; 95% CI: 0.86;0.89), regular physical activity (OR=0.78; 95% CI: 0.65;0.94) and hormone replacement therapy (OR=0.43; 95% CI: 0.33;0.56) had a protective effect on bone mass. Risk factors significantly associated with osteoporotic fractures were age (OR=1.05; 95% CI: 1.04;1.06), time since menopause (OR=4.12; 95% CI: 1.79;9.48), familial history of hip fracture (OR=3.59; 95% CI: 2.88;4.47) and low BMD (OR=2.28; 95% CI: 1.85;2.82). CONCLUSIONS: Advanced age, menopause, low-trauma fracture and current smoking are major risk factors associated with low BMD and osteoporotic fracture. The clinical use of these parameters to identify women at higher risk for fractures might be a reasonable strategy to improve the management of osteoporosis. OBJETIVO: Estimar la prevalencia y analizar los factores de riesgo asociados con osteoporosis y fractura por bajo impacto entre mujeres. MÉTODOS: Estudio transversal realizado con 4.332 mujeres encima de 40 años de edad provenientes de atención primaria de salud en el área metropolitana de la gran Sao Paulo, SP, entre 2004 2007. Datos antropométricos y ginecológico y relativos a hábitos de vida, fractura previa, antecedentes personales, ingestión alimentaria y actividad física fueron evaluados por medio de entrevista individual y cuantitativa. Fractura por bajo impacto fue definida como decurrente de caída de la propia altura o menos en individuos con más de 50 años de edad. Modelos de regresión multivariada y logística analizaron, respectivamente, la densidad ósea y la fractura por osteoporosis, como variables dependientes y todas las otras como independientes. El nivel de significancia estadística establecido fue p<0,05. RESULTADOS: La prevalencia de osteoporosis y de fracturas por fragilidad ósea fue de 33% y 11,5%, respectivamente. Los principales factores de riesgo asociados con baja densidad ósea fueron edad (OR=1,07; IC 95%: 1,06;1,08), menopausia (OR=2,16; IC 95%: 1,49;3,14), fractura previa (OR=2,62; IC 95%: 2,08;3,29) y tabaquismo actual (OR=1,45; IC 95%: 1,13;1,85). Por otro lado, elevado IMC (OR=0,88; IC 95%: 0,86;0,89), actividad física regular (OR=0,78; IC 95%: 0,65;0,94) y terapia hormonal actual (OR=0,43; IC 95%: 0,33;0,56) desempeñaron papel protector. Los factores de riesgo significantemente relacionados con fractura por osteoporosis fueron edad (OR=1,05; IC 95%: 1,04;1,06), menopausia (OR=4,12; IC 95%: 1,79;9,48), historia familiar de fractura de cuadril (OR=3,59; IC 95%: 2,88;4,47) y baja densidad ósea (OR=2,28; IC 95%: 1,85;2,82). CONCLUSIONES: Edad avanzada, menopausia, fractura previa por bajo impacto y tabaquismo actual son los principales factores de riesgo asociados con baja densidad ósea y esta, con las fracturas por fragilidad ósea. El uso clínico de estos parámetros para identificar mujeres de mayor riesgo para fracturas puede ser una estrategia interesante para mejorar el abordaje de la osteoporosis. OBJETIVO: Estimar a prevalência e analisar os fatores de risco associados com osteoporose e fratura por baixo impacto entre mulheres. MÉTODOS: Estudo transversal realizado com 4.332 mulheres acima de 40 anos de idade provenientes de atendimento primário de saúde na área metropolitana da Grande São Paulo, SP, entre 2004 e 2007. Dados antropométricos e ginecológicos e relativos a hábitos de vida, fratura prévia, antecedentes pessoais, ingestão alimentar e atividade física foram avaliados por meio de entrevista individual e quantitativa. Fratura por baixo impacto foi definida como decorrente de queda da própria altura ou menos em indivíduos com mais de 50 anos de idade. Modelos de regressão multivariada e logística analisaram, respectivamente, a densidade óssea e a fratura por osteoporose como variáveis dependentes e todas as outras como independentes. O nível de significância estatística estabelecido foi p < 0,05. RESULTADOS: A prevalência de osteoporose e de fraturas por fragilidade óssea foi de 33% e 11,5%, respectivamente. Os principais fatores de risco associados com baixa densidade óssea foram idade (OR = 1,07; IC 95%: 1,06;1,08), menopausa (OR = 2,16; IC 95%: 1,49;3,14), fratura prévia (OR = 2,62; IC 95%: 2,08;3,29) e tabagismo atual (OR = 1,45; IC 95%: 1,13;1,85). Por outro lado, elevado IMC (OR = 0,88; IC 95%: 0,86;0,89), atividade física regular (OR = 0,78; IC 95%: 0,65;0,94) e terapia hormonal atual (OR = 0,43; IC 95%: 0,33;0,56) desempenharam papel protetor. Os fatores de risco significativamente relacionados com fratura por osteoporose foram idade (OR = 1,05; IC 95%: 1,04;1,06), menopausa (OR = 4,12; IC 95%: 1,79;9,48), história familiar de fratura de quadril (OR = 3,59; IC 95%: 2,88;4,47) e baixa densidade óssea (OR = 2,28; IC 95%: 1,85;2,82). CONCLUSÕES: Idade avançada, menopausa, fratura prévia por baixo impacto e tabagismo atual são os principais fatores de risco associados com baixa densidade óssea, a qual se associa com as fraturas por fragilidade óssea. O uso clínico desses parâmetros para identificar mulheres de maior risco para fraturas pode ser uma estratégia interessante para melhorar a abordagem da osteoporose.